Modelling anti-icing of railway overhead catenary wires by resistive heating. (November 2019) - Nilsson, Fritjof; Moyassari, Ali; Bautista, Ángela; Castro, Abraham; Arbeloa, Ignacio; Järn, Mikael; Lundgren, Urban; Welinder, Jan; Johansson, Kenth
Highlights: Anti-icing of railway overhead contact lines, using resistive heating, was examined. Climate chamber measurements and FEM analysis was utilized. Wind velocity, wind direction, external temperature and cable diameter was varied. Predictive analytical cable temperature equations were developed. The simulations and models were validated with experimental data. Abstract: Aggregation of ice on electrical cables and apparatus can cause severe equipment malfunction and is thus considered as a serious problem, especially in arctic climate zones. In particular, cable damage caused by ice accumulation on railway catenary wires is in wintertime a common origin for delayed trains in the northern parts of Europe. This study examines how resistive heating can be used for preventing formation of ice on metallic, non-insulated electrical cables. The heat equation and the Navier Stokes equations were solved simultaneously with FEM in 3D in order to predict the cable temperature as function of external temperature, applied voltage, wind speed, wind direction, and heating time. An analytical expression for the heat transfer coefficient was derived from the FEM simulations and it was concluded that the influence of wind direction can typically be neglected. Experimental validation measurements were performed on Kanthal cables in a climate chamber, giving temperature increase results in good agreement with the simulation predictions. The resistive heating efficiency, i.e. the ratio between applied electrical energy and resulting thermal energy, was found to be approximately 68% in this particular study.